Editorial: Representing the Ancient World through Data - Andrea Farina; Paola Marongiu; Mar A. Rodda (Journal of Open Humanities Data)
In this Editorial Paper, we present the special collection Representing the Ancient World through Data, a dedicated platform for publishing data papers in the field of Ancient World studies. As data-driven methodologies increasingly become integral to research in these areas, this collection serves as a key venue for showcasing diverse datasets. Covering a wide range of disciplines – from linguistics to geography, history, and religion – the 18 articles included in the collection describe datasets compiled following different and innovative approaches. The success of our special collection reflects a growing recognition among scholars of the importance of describing the process of data creation and the reuse potential of the final product. Our hope is that this special collection inspires further engagement with data-driven research, promoting innovation and interdisciplinary collaboration within the field.